2012
DOI: 10.1590/s1679-45082012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Ertapebem disk performance to predict Klebsiella pneumoniae carbapenemase produced by Gram-negative bacilli isolated in a São Paulo city public hospital

Abstract: Objective: To evaluate ertapenem disk performance to predict Klebsiella pneumonie carbapenemase production by Gram-negative bacilli. Methods: All Gram-negative bacilli isolated between January 2010 and June 2011 were tested by disk diffusion (Oxoid™) for sensitivity to ertapenem, meropenem and imipenem. Resistant or intermediate sensitivity strains (diameter ≤22 mm for ertapenem) were also tested for the blaKPC gene by polymerase chain reaction. Disk predictive positive value for Klebsiella pneumoniae carbapen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
1
5
0
6
Order By: Relevance
“…(9; 19.1%). These results are in agreement with the study conducted by Almeida et al ( 14 ) in the city of São Paulo (SP), in which, from 40 samples that presented with the bla KPC gene (PCR), 38 were K. pneumoniae and 2 were Enterobacter cloacae . Still in this study, the authors found that the isolates originated from different clinical specimens such as urine, tracheal secretion, blood culture, pancreatic abscess secretion, and the largest isolation occurred in a rectal swab, representing 42.5%, ( 14 ) different from the present study in which the greatest isolation was in tracheal aspirates (12; 25%), followed by urine (10; 21%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…(9; 19.1%). These results are in agreement with the study conducted by Almeida et al ( 14 ) in the city of São Paulo (SP), in which, from 40 samples that presented with the bla KPC gene (PCR), 38 were K. pneumoniae and 2 were Enterobacter cloacae . Still in this study, the authors found that the isolates originated from different clinical specimens such as urine, tracheal secretion, blood culture, pancreatic abscess secretion, and the largest isolation occurred in a rectal swab, representing 42.5%, ( 14 ) different from the present study in which the greatest isolation was in tracheal aspirates (12; 25%), followed by urine (10; 21%).…”
Section: Discussionsupporting
confidence: 93%
“…Ertapenem constituted a marker of resistance to carbapenems, and could be directly related to the KPC enzyme or to other mechanisms that decrease sensitivity to these antimicrobials in a specific way, such as with the production of other beta-lactamases and loss of purines. ( 14 ) In the study by Bratu et al, which involved 62 isolates of K. pneumoniae that produced KPC, the resistance to carbapenems imipenem, meropenem, and ertapnenem was 98%, 96%, and 100%, respectively. In this study, the authors concluded that the resistance to ertapenem represented the most sensitive clinical test for detection of KPC production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os dados são preocupantes, uma vez que polimixina B é considerado tratamento de última linha para essas infecções graves. Já o percentual de resistência a ertapenem era esperado, pois para os carbapenêmicos já é considerado um marcador de resistência, podendo ou não estar associado à produção enzimática 37 .…”
Section: Discussionunclassified